2008
DOI: 10.1186/1476-511x-7-38
|View full text |Cite
|
Sign up to set email alerts
|

Taurine reduces the secretion of apolipoprotein B100 and lipids in HepG2 cells

Abstract: Background: Higher concentrations of serum lipids and apolipoprotein B100 (apoB) are major individual risk factors of atherosclerosis and coronary heart disease. Therefore ameliorative effects of food components against the diseases are being paid attention in the affluent countries. The present study was undertaken to investigate the effect of taurine on apoB secretion and lipid metabolism in human liver model HepG2 cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 22 publications
0
43
0
1
Order By: Relevance
“…More recently the effects of taurine on cholesterol and lipid levels have been reported[49]. Zhang et al (2003) showed a hypocholesterolemic effect of dietary taurine in overweight adults[50] and in a 2008 study, taurine was shown to reduce the secretion of apolipoprotein B100 and lipids in liver cells[51]. Hence, taurine supplementation may be beneficial for the prevention of artherosclorosis.…”
Section: Functions Of Vanin In Diseasementioning
confidence: 99%
“…More recently the effects of taurine on cholesterol and lipid levels have been reported[49]. Zhang et al (2003) showed a hypocholesterolemic effect of dietary taurine in overweight adults[50] and in a 2008 study, taurine was shown to reduce the secretion of apolipoprotein B100 and lipids in liver cells[51]. Hence, taurine supplementation may be beneficial for the prevention of artherosclorosis.…”
Section: Functions Of Vanin In Diseasementioning
confidence: 99%
“…Yanagita T et al noted that the cellular cholesterol levels decreased and synthesis of cholesterol ester was inhibited when the HepG2 cells were incubated in DMEM medium with taurine for 24 h [22]. Lam NV et al reported that taurine significantly increased CYP7A1 mRNA level and promoted cholesterol degradation regardless of whether the HepG2 cells were cultured under the conditions of high cholesterol or not [7], and Hoang HM et al indicated that CYP7A1 mRNA levels increased 3 times when the H4IIE cells were treated with taurine [23].…”
Section: Discussionmentioning
confidence: 99%
“…In a study conducted by Yanagita and colleagues taurine is found to reduce the secretion of apolipoprotein B100 and lipids in HepG2 cells [43]. Higher concentrations of serum lipids and apolipoprotein B100 (apoB -essential structural component of VLDL and LDL) are major individual risk factors of atherosclerosis and coronary heart disease.…”
Section: Taurinementioning
confidence: 99%